An Analysis of Positive and Negative Politeness Strategies used by Desi Anwar in CNN Indonesia INSIGHT with Desi Anwar on Trans TV - Misnarni Misnarni; Sufiyandi Sufiyandi; Asridayani Asridayani (Krinok:Jurnal Linguistik Budaya, 2019)
The research analyzes about “An Analysis of Positive and Negative Politeness Strategies used by Desi Anwar in CNN Indonesia INSIGHT with Desi Anwar on Trans TV.This research has two objectives, the first purpose is to find out and describe kinds of positive and negative politeness strategies used by Desi Anwar. The second one is to describe the factors influencing the positive and negative politeness strategies used by Desi Anwar. This research was conducted by using descriptive qualitative method through applying three steps. The first one was by collecting data through three ways: (1) non participant technique, (2) download technique and (3) writing technique. Then, the writer uses an identity method in analyzing the data. Identity method is the method used to assess or that are beyond language, regardless of the language and does not become part of the language  (Sudaryanto,1993). The last, in presenting the data, the writer uses formal and informal method. Formal method is  the way to analyze the data with the symbol or the sign, informal method is the way to analyze the data with verbal word The results of the research. Then the factors influence the choice uses of politeness strategies used by Desi Anwar. There are three factors. They are occupation, social status and formality.  Key Words: Positive Politeness Strategy, Negative Politeness Strategy